Mitigating ammonium toxicity in strawberry cultivation: effective fertilization practices for sustainable crop production - Ghulam Sarwar; Rutaba Noor; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Younus; Muhammad Waqar Hassan; Muhammad Sajid-ur-Rehman; Muhammad Tahir Naseem; Gadah Albasher; Mohammad Javed Ansari; Rana Tauqeer Ahmad (BMC Plant Biology)
Abstract Nitrogen is crucial for plant growth, but deficiency and excess can harm plants. Fertilizers like Diammonium Phosphate (DAP), which releases ammonium (NH4 +), are common, yet over-application can cause NH4 + toxicity, resulting in stunted roots and leaf damage. This study investigated the impact of NH4 + toxicity on strawberry growth, yield, and fruit quality to inform better fertilization practices. The experiment was conducted at The Islamia University of Bahawalpur, Pakistan. Five treatments with varying DAP rates (0 g, 4 g, 7 g, 10 g, and 13 g per plant) were applied to strawberry plants in a completely randomized design with four replications. Photosynthetic pigments, hydrogen peroxide (H2O2), malondialdehyde (MDA), electrolyte leakage (EL), and yield parameters were measured. The 4 g DAP treatment yielded the highest chlorophyll-a (0.5775 mg/g FW) and total chlorophyll content (0.705 mg/g FW). However, increasing DAP doses led to a decline in chlorophyll-a, chlorophyll-b, and total chlorophyll content, with the 13 g DAP treatment exhibiting the lowest levels. H2O2 content increased with higher DAP doses, with the 13 g DAP treatment showing the highest value (75 µmol/g FW). Higher DAP doses also increased MDA content and EL, indicating oxidative stress and membrane damage. The 4 g DAP treatment showed minimal changes in H2O2 and MDA content. Moderate DAP levels (4 g per plant) enhanced strawberry growth, yield, and photosynthetic activity, while higher doses caused significant stress, leading to reduced growth and yield. Managing NH4 + levels in fertilization is crucial for optimizing strawberry production. Therefore, moderate doses of DAP (ammonium ion) should be used to avoid ammonium toxicity.